Characterization of Dysplastic Aberrant Crypt Foci in the Rat Colon Induced by 2-Amino-1-Methyl-6-Phenylimidazo[4,5-b]Pyridine - Ochiai, Masako (American Society for Investigative Pathology, 2003)
The multistage model of colon carcinogenesis is well established in both humans and experimental animals, and aberrant crypt foci (ACF) are generally assumed to be putative preneoplastic lesions of the colon. However, morphological analyses of ACF have suggested that they are highly heterogeneous in nature and their role in tumorigenesis is still controversial. To better understand the biological significance of ACF in carcinogenesis, morphological and genetic analyses were performed using a rat colon cancer model induced by a food-borne colon carcinogen, 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP). ACF of different sizes were collected at weeks 6, 18, 25, and 32 after three cycles of 2-week PhIP feeding (400 ppm in diet) with 4-week intervals on a high-fat diet, and a total of 110 ACF, representing approximately three-quarters of the total ACF, were subjected to histological evaluation. Thirty (27%) were diagnosed as dysplastic ACF, based on cytological and structural abnormalities of crypts. Dysplastic ACF were detected even at week 6 (0.4 per rat), and the numbers increased slightly at later time points, being 0.8, 1.4, and 0.8 per rat at weeks 18, 25, and 32, respectively. The sizes of these dysplastic ACF varied widely from 1 to 16 crypts and 50% (15 of 30) were composed of less than 4 crypts. Immunohistochemical analysis revealed that 83% (25 of 30) of dysplastic ACF demonstrated β-catenin accumulation; 22 only in the cytoplasm and 3 in both the cytoplasm and nucleus, the latter manifesting a higher grade of dysplasia as compared with the former. Seven dysplastic ACF harbored β-catenin mutations at codon 32, 34, or 36 in exon 2, and one had an Apc mutation at the boundary of intron 10 and exon 11. Mutations at these sites were also commonly found in colon tumors induced by PhIP. The results of our present study indicate that dysplastic ACF, which accounted for approximately one-fourth of the total ACF, are preneoplastic lesions of colon cancers induced by PhIP in rats.